How Nokia failed to nail the Smartphone market - Harry Bouwman; Christer Carlsson; Joanna Carlsson; Shahrokh Nikou; Anna Sell; Pirkko Walden (International Telecommunications Society (ITS), 2014)
In this paper we will discuss Nokia's struggle to find a sustainable approach to the Smartphone market. The findings are based on (i) a review of Nokia's history, and specifically on how Nokia dealt with introducing new, more or less smart handsets, (ii) on interviews with managers from Nokia and (iii) on data collected on mobile phone usage in 2003 -2011 in Finland. We contribute to insights on how a company with an active innovation policy, product launch and market segmentation strategy failed to maintain its dominance on the mobile handset market.
Keywords: 330